Fibromyalgia and Diet-Related Diseases: Does Health Professional Advice Make Sense? - Laura-Isabel Arranz; Miguel-Ángel Canela; Magda Rafecas (Journal of Pharmacy and Nutrition Sciences, 2011)
Many people in the world suffer from fibromyalgia (FM), a rheumatic disease of unknown ethiopathophysiology and without an effective treatment. Patients do not have a good quality of life and cannot maintain normal daily activity. FM commonly occurs with other diseases, some of them, like irritable bowel syndrome, obesity, or some food allergies or intolerances, are related or affected by diet. Non-scientific information addressed to patients regarding the benefits of nutrition is widely available, and they are used to trying non-evidenced strategies. The aim of this paper is to make a first reflection on the relevance of diet related diseases in FM patients, to reinforce investigation in this field and highlight the importance of health professional advice regarding diets and use of food supplements. An internet based survey was prepared and offered to answer in a specific FM website. Patients were asked about hypertension, hypercholesterolemia, hypertriglyceridemia, irritable bowel syndrome, food allergies and intolerances, and overweight or obesity. Ninety seven persons answered to the survey, two men and ninety five women. Irritable bowel syndrome and excess weight (overweight and obesity) were the most reported diet-related diseases. In the third position were food allergies or intolerances, and in the fourth hypertension. Diet-related diseases are frequent in FM patients, who even sometimes suffer more than two. Therefore, more investigation and dietary advice seems to be necessary to these patients to improve their diets, taking into account FM but also other pathologies, to keep an optimum nutritional status and maintain a normal weight.